Equity, Diversity and Canadian Labour - Legault, Marie-Josée (Relations industrielles / Industrial Relations, 2009)
The article reviews the book, "Equity, Diversity and Canadian Labour," edited by Gerald Hunt and David Rayside.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z